2015
DOI: 10.1088/0029-5515/55/4/043009
|View full text |Cite
|
Sign up to set email alerts
|

High density LHRF experiments in Alcator C-Mod and implications for reactor scale devices

Abstract: Abstract. Parametric Decay Instabilities (PDI) appear to be an ubiquitous feature of Lower Hybrid Current Drive (LHCD) experiments at high density. In density ramp experiments in Alcator C-Mod and other machines the onset of PDI activity has been well correlated with a decrease in current drive efficiency and production of fast electron Bremsstrahlung. However whether PDI is the primary cause of the "density limit", and if so by exactly what mechanism (beyond the obvious one of pump depletion) has not been cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…[13]. An alternate approach to recover the current drive in a diverted configuration was discovered last year when we measured the dependency of CD efficiency in a wide range of plasma current [14]. Figure 2 compares the SOL …”
Section: Experimental Progresses To Improve Lhcd At High Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…[13]. An alternate approach to recover the current drive in a diverted configuration was discovered last year when we measured the dependency of CD efficiency in a wide range of plasma current [14]. Figure 2 compares the SOL …”
Section: Experimental Progresses To Improve Lhcd At High Densitymentioning
confidence: 99%
“…16 in Ref. 14). To make a quantitative comparison with the observation, we estimated the LH power by the sum of ray power propagating near the probe location.…”
Section: -4mentioning
confidence: 99%
“…As a result, the LH waves launched at the outer mid-plane are weakly absorbed on a single-pass, and the waves may undergo multiple parasitic edge loss mechanisms [9,10,11,12,13] at the plasma edge before being absorbed via electron Landau damping (ELD) in the plasma core. In particular, the wave-power reaching the high field side (HFS) of the C-Mod tokamak was found to decrease as density increases above ̅ = 1.0 × 10 20 m −3 [14]. Further, a recent ray-tracing modeling study [15] indicates that 2 collisional absorption could explain the observed anomalous decrease in hard X-ray count rates (thus fast electron populations) in high density plasmas, consistent with the experimental observation of the enhanced ionization rate in the active divertor region with the applied LH power [2].…”
mentioning
confidence: 99%
“…In all cases, 2 remains high above 90%. of the onset of ion cyclotron parametric decay instabilities, which may be linked to the observed LHCD density limit problem [14]. Given the frequency separation, this instability is expected to occur at the LFS edge on the first pass from the launcher to the plasma.…”
mentioning
confidence: 99%
“…The importance of introducing such a current drive method was already recognized in the ARIES reactor studies where it was necessary to introduce the fast lower hybrid wave (helicon wave in current use) in the 1 GHz range to provide some of the necessary driven current in the outer region of the plasma core, yet well inside the pedestal region [3]. Previous work postulated [4] that significant levels of PDI would be unlikely in such experiments due to the weaker RF electric fields of these predominantly electromagnetic waves, in contrast to those of the quasilongitudinal (electrostatic) slow lower hybrid wave [5,6,7,8]. In this work we show that this is not necessarily the case under present day experimental conditions in medium size tokamaks, e.g., DIII-D, where 1 MW of RF power at 476 MHz is proposed to be injected using a "comb-line" traveling wave antenna [2].…”
Section: Introductionmentioning
confidence: 99%